Paeonol Attenuated Inflammatory Response of Endothelial Cells via Stimulating Monocytes-Derived Exosomal MicroRNA-223 - Liu, Yarong; Li, Chao; Wu, Hongfei; Xie, Xianmei; Sun, Ying; Dai, Min (Frontiers in Pharmacology, 2018)
Introduction: Paeonol, an active compound isolated from the radix of Cortex Moutan, has been shown to have anti-atherosclerosis effects by regulating blood cells’ function and protecting vascular cells injury. Besides, emerging evidences has proven that exosomes might play a pivotal role in intercellular communication by transmiting proteins and microRNAs from cell to cell. However, the relationship between monocytes-derived exosomal microRNA-223 and vascular inflammation injury along with paeonol’ effects are still not clear. Objective: Our study aimed to explain whether paeonol’s protective effect on inflammatory response is related to the regulation of exosomal microRNA-223 in the VECs. Methods: ApoE-/- mice were fed with high fat diet to replicate the AS model. HE staining and immunohistochemistry was used to detect inflammatory response of aorta. The expression of IL-1β and IL-6 were detected by ELISA. Western blot was used to detect the expression of STAT3, pSTAT3, ICAM-1 and VCAM-1. qRT-PCR was used to detect miR-223 expression. Exosomes were extracted from THP-1 cells by differential centrifugation and observed by transmission electron microscope. Observation of exosomes uptake into HUVECs was realized by laser microscopy. MiR-223 target gene was detected by double luciferase gene report test. Results: In vivo experiments confirmed that paeonol restricted atherosclerosis development and increased miR-223 expression, inhibited STAT3 pathway in ApoE-/- mice. In vitro, miR-223 showed robust presence in THP-1 cells and undetectable in HUVECs. And we had observed that miR-223 could be internalized from THP-1 cells into HUVECs taking exosomes as a carrier. Paeonol obviously increased miR-223 expression in co-cultured HUVECs and exosomes in concentration dependent manner, compared to LPS group. In addition, paeonol relieved inflammatory secretion, adhesion and STAT3 expression in HUVECs, which could be inverted after miR-223 inhibitor transfection into THP-1 cells. Conclusion: Paeonol could increase the expression of miR-223 in THP-1 derived exosomes and in HUVECs after uptake of exosomes, whereas decrease the expression of STAT3, p-STAT3 in HUVECs. Ultimately paeonol decreased the expression of IL-1β, IL-6, ICAM-1, VCAM-1 in HUVECs and alleviated adhesion of THP-1 cells to HUVECs.